The Combination of Butyl Para-Aminobenzoate and Iodoform as a Secondary Prevention of Dry Socket: A Systematic Review - Kusumastiwi, Pipiet Okti; Hendrartini, Julita; Dwiprahasto, Iwan (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Dry socket is the most common post-operative complication following a dental extraction and one of the most studied complications in dentistry. Many researchers have attempted to find a successful method for its primary prevention. However, this area remains controversial as no single method has gained universal acceptance. Therefore, secondary prevention of this case is still needed to prevent the continuing effects of dry sockets and other complications resulting from inadequate dry socket treatment. One of the most common treatments of dry socket is a combination of butyl aminobenzoate, eugenol, and iodoform. The presence of this medicament in a healing socket also has been shown to cause a foreign body reaction, delayed healing, and prolonged pain. AIM: The objective of the study was to compare the treatment results of dressing with a combination of butyl aminobenzoate, eugenol, and iodoform and other treatments for dry socket regarding the result of pain’s relief and healing of sockets. METHODS: Searches were conducted in the following electronic databases: PubMed, ProQuest, and EBSCO. The inclusion criteria were randomized controlled trial with a minimum of 10 patients, published from 2009 to 2019, and written in English. The exclusion criteria were case reports and non-human studies. RESULTS: Ten articles were found in an initial search, of which six were selected for a systematic review. Alternative treatment identified included zinc oxide eugenol (ZOE), a combination of polymyxin B sulfate, tyrothricin, neomycin sulfate, tetracaine hydrochloride, freeze-dried pledget containing acemannan hydrogel, plasma rich in growth factors, and low-level laser therapy, Er:Cr:YSGG, and laser diodes. CONCLUSION: All treatments included in the review have the aim to relief the patient’s pain. Given the heterogeneity of interventions and the type of measurement scale, the results are difficult to compare. The combination of butyl aminobenzoate, eugenol, and iodoform is superior compared to ZOE for pain relief and socket healing. For socket healing and pain relief from the 2nd day after the extraction, it appears that several alternative treatments are superior to the combination of butyl aminobenzoate, eugenol, and iodoform.